Engineering Mechanics - Pytel, Andrew (Brooks/Cole, 1999)
Nationally regarded authors Andrew Pytel and Jaan Kiusalaas bring a depth of experience to the Second Editions of ENGINEERING MECHANICS: STATICS AND DYNAMICS that can't be surpassed. They have refined their solid coverage of this material without overloading it with extraneous detail. Their extensive teaching experience at The Pennsylvania State University gives them first-hand knowledge of students' learning skill levels and how the study of mechanics needs to tie to the real world. Their presentation is designed to teach students how to effectively analyze a problem before plugging numbers into formulas. This approach benefits students tremendously as they encounter real life problems that may not always fit into standard formulas. These books are designed with a rich, concise, one-color presentation at a substantially lower cost than competing texts